Occupational hazards in welding industry - Ziba Loukzadeh; Mona Torab Jahromi (طب کار)
Background: Welding is considered as an essential component of many industries and the National Institute for Safety and Health in 1988 estimated that at least two million workers are working as welder so knowing how to control occupational exposures in this industry, to protect and promote the health of welders is essential. Methods: This reviewing article consists of several parts, including: definition and history of welding industry, introduction a variety of welding methods, occupational exposures in the welding industry, diseases caused by occupational exposures in this industry, hazard control techniques in welding industry and welders, health monitoring. Results: Welders are exposed to a variety of physical and chemical hazards and a level of hazardous exposure in different welding methods also is different. Among the exposure factors that could be harmful, gases and fumes, heat stress, noise, non-ionizing radiations, ergonomic exposures and safety hazards are noted. Due to this exposure, welders are at risk of respiratory diseases such as rhinitis, asthma, chronic bronchitis and emphysema, and ... as well as diseases caused by harmful physical agents. Conclusion: After identification of exposures, using appropriate control methods including substitution, general and local ventilation, shielding protection, personal protective equipment, periodically health monitoring of welder, welder training, and compliance with laws and standards.